Dendritic growth at the solidification interface in selective laser melting of 316L steel - Gruzd, SvetlanaSvetlana Anatol’yevna; Mosin, Anatoliy Igorevich; Krivilyov, Mikhail Dmitriyevich (Computational Continuum Mechanics, 2023)
Metal powder-based additive manufacturing is a rapidly developing area of mechanical engineering mainly related to the active utilization of 3D printers in the industry. One of the important characteristics of the products obtained using this technology is the strength which depends on the initial microstructure of the material. The morphology of the products manufactured by selective laser melting (SLM) is of dendritic-cellular type. In this paper, the problem of determining the characteristic size of dendrites formed during high-speed solidification at the boundary of the molten pool by selective laser melting of a 316L stainless steel powder layer is considered. Input parameters are defined as the macro parameters of the system under study, such as the thermodynamic properties of a stainless steel melt, the speed of a laser beam, as well as the orientation angle of the tail of the molten pool, where the main section of the crystallization front is located. The mathematical model is based on the Ivantsov approximation of parabolic-shaped crystals, which is found as an approximate solution of the axisymmetric problem of heat and mass transfer. A numerical simulation is performed using a two-dimensional dendritic growth model by Alexandrov and Galenko. The model describes the steady growth of a dendrite in a two-component system in the presence of convection in a solidifying melt. Using this model, the authors propose a method for calculating the solidification velocity and the tip diameter of dendrites, depending on the macroscopic parameters, which in turn can be the control parameters for obtaining the specified properties of the manufactured product. The calculated values are compared to the results of the experimental investigation by transmission electron microscopy of 316L steel samples manufactured by selective laser melting.